Blockade of Interleukin‐17 Restrains the Development of Acute Lung Injury. (March 2016) - Li, Q.; Gu, Y.; Tu, Q.; Wang, K.; Gu, X.; Ren, T.
Abstract: The acute respiratory distress syndrome (ARDS), a clinical complication of severe acute lung injury (ALI) in humans, is a leading cause of morbidity and mortality in critically ill patients. Here, we explored the association between IL‐17 and development of ALI using LPS‐induced murine model. We found that IL‐17 level was elevated in bronchoalveolar lavage (BAL) fluid of ALI mice. Upregulation of IL‐17 resulted in increased severity of ALI as evidenced by decreased body weight and survival rate, elevated level of total protein and albumin in BAL fluid, as well as more apparent histopathology changes of lung. Induction of ALI was impaired in IL‐17‐deficient mice. Management of IL‐17 could modulate LPS‐induced pulmonary inflammation, as reflected by the total cell and neutrophil counts, proinflammatory cytokines, as well as chemokines in BAL fluid. Of note, blockade of IL‐17 effectively inhibited the lung inflammation and alleviated ALI severity. Finally, we confirmed the clinical relevance and found that IL‐17 expression was elevated and associated with the disease severity in patients with ARDS. In essence, IL‐17 was crucial for development of ALI, suggesting a potential application for IL‐17‐based therapy in clinical practice.